Autoimmune polyendocrine syndromes: clues to type 1 diabetes pathogenesis - Husebye, Eystein S. (2010)
Autoimmune diseases like type 1 diabetes are complex in their pathogenesis. One approach to improving our understanding of type 1 diabetes is the study of diseases that represent more extreme examples of autoimmunity. Autoimmune polyendocrine syndromes (APS) are relatively rare diseases that often include type 1 diabetes as part of the disease phenotype. Recently there has been tremendous progress in unraveling some of the underlying mechanisms of APS. Here we highlight the APS disorders with the perspective of the clues they can offer to the pathogenesis and treatment of type 1 diabetes.